An Analysis of Translation Techniques Used in Powell’s Poem “You Are My Everything” - R Bunga Febriani (Scopus ID 57217300982); Rohayani Rohayani; Syafryadin Syafryadin (Universitas Bengkulu, 2021)
This study investigated the types of translation techniques. This study used the qualitative method and the forms of data were document and transcript of English poem and Indonesian poem, it included to the content analysis. The data that obtained was the translation techniques. The population and sample of this study was both of the English and Indonesian poem as the population and the sample poem that was found in the English into Indonesian poem. The results of analysis concluded that literal translation, deletion, addition and transposition were techniques used by the translator in translating poem “You are My Everything” by Powell. Meanwhile, the results also revealed that translation techniques are dominantly used by the translator in translating poem “You are My Everything” by Powell is literal translation. In conclusion, this study consists of four translation techniques there are literal translation, addition, deletion, and transposition and literal translation translation technique is dominantly used by the translator which was used 24 (twenty four) times. It is recommended to the reader for increase the reading comprehension, and the other researcher to understand, then using translation the researcher more understand about the meaning of text and knowing the translation techniques used to translate text in target language.